GAMBARAN DUKUNGAN KELUARGA PASIEN PASCA STROKE DALAM MENJALANI REHABILITASI - Renni Okwari; Wasisto Utomo; Rismadefi Woferst (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Post stroke patients in rehabilitation need family support for recovery. Family support is a form of positif behavior thatfamily provide during rehabilitation because rehabilitation takes a long time. The aim of this study to identify thecharacteristic and family support of post stroke patients in rehabilitation. The design of this study was retrospectivewith simple descriptive approach. The sampling technique in this study was purposive sampling with a total sample 33respondents. The result of this study can be described that from the 33 respondents, there were 18 respondents (55%) inthe elderly, 17 respondents (52%) were the women, 9 respondents (27%) were SMA, 33 respondents (100%) were notwork, and 28 respondents (85%) have high family support. The result of this study recommend heath service to motivatepatients and families to go to rehabilitation.Keyword : Family Support, Rehabilitation, Stroke